Current status of Bifurcation stent systems - gaurav singhal (Publisher: Shahid Beheshti University of Medical Sciences)
ACoronary bifurcation lesions are frequently observed and remain a challenging patient population for successful treatment. Currently, the provisional approach of treatment is considered the first-line method of treatment. Many dedicated bifurcation stents and newer treatment approaches such as drug-coated balloons and bioresorbable scaffolds are also particularly attractive concepts. The aim of this article is to review the current treatment approaches for coronary bifurcation lesions, mainly the dedicated bifurcation stent systems while briefly covering the related topics of provisional and two-stent procedures of treatment and the current status of drug-coated balloons and bioresorbable scaffolds. This article highlights the critical trials involving these strategies. We searched PubMed, Google Scholar, Medline and ClinicalTrials.gov to identify all the relevant trials assessing the safety and efficacy of dedicated bifurcation stent systems, drug-coated balloons vs. other traditionally used coronary stents. A debate still prevails to treat coronary bifurcation lesions optimally. Provisional stenting strategy remains the gold standard for treating a majority of coronary bifurcation lesions, but the two-stent approach can be indicated for some lesions. More long-term follow-up trials are required to concretely define the role of newer treatment approaches such as dedicated bifurcation stents, drug-coated balloons, and bioresorbable scaffolds.